2003
DOI: 10.1046/j.1365-2389.2003.51313.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Total Cholesterol and Increased Risk of Dying: Are Low Levels Clinical Warning Signs in the Elderly? Results from the Italian Longitudinal Study on Aging

Abstract: Subjects with low TC levels (<189 mg/dL) are at higher risk of dying even when many related factors have been taken into account. Although more data are needed to clarify the association between TC and all-cause mortality in older individuals, physicians may want to regard very low levels of cholesterol as potential warning signs of occult disease or as signals of rapidly declining health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 31 publications
5
46
0
1
Order By: Relevance
“…Lower serum total cholesterol levels among older adults are predictive of all-cause mortality (28,29) and functional decline (30). In the Three-City cohort study, with 6,141 participants aged ≥65 years and followed up for 7 years, high triglycerides (≥1.7 mmol/L) were significantly associated with the incidence of mobility limitations (using the Rosow and Breslau scale) and with worse scores in the basic and instrumental activities of daily living scales (31).…”
Section: Discussionmentioning
confidence: 99%
“…Lower serum total cholesterol levels among older adults are predictive of all-cause mortality (28,29) and functional decline (30). In the Three-City cohort study, with 6,141 participants aged ≥65 years and followed up for 7 years, high triglycerides (≥1.7 mmol/L) were significantly associated with the incidence of mobility limitations (using the Rosow and Breslau scale) and with worse scores in the basic and instrumental activities of daily living scales (31).…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] Several pos-sible explanations have been proposed to explain this apparent paradox, mainly the idea of selective mortality, which is a hypothesis that many individuals with high levels of total cholesterol might experience an earlier onset of severe coronary heart disease, leading to disproportionately greater mortality before reaching an advanced age. [76][77][78] It has also been argued that low cholesterol levels may reflect an underlying serious disease or poor nutritional status, which could predispose to a poor outcome after stroke. 76,[79][80][81] Indeed, previous studies have shown a graded negative relationship between serum cholesterol levels and the risk of nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In several large-scale studies, all-cause mortality was inversely related to cholesterol: lower cholesterol was associated with higher all-cause mortality and higher cholesterol was associated with lower all-cause mortality. 37,38 The reasons for these results remain unclear. The findings in our study may contribute to an understanding of these results: higher cholesterol favors the development of minor stroke associated with lower mortality.…”
Section: Cholesterol and Stroke Survivalmentioning
confidence: 99%